Heart failure with reduced ejection fraction: Should we submit patients without angina to coronary angiography? - Silva, F (2015)
Coronary artery disease (CAD) accounts for about two-thirds of cases of heart failure with reduced ejection fraction (HFrEF) [1]. Angina symptoms and cardiovascular risk factors (CVRF) are not sufficient to establish an ischemic etiology and according to recommendations coronary angiography (CA) is the gold standard [1–3]. There is a paucity of information on the performance of CA for detecting CAD in HFrEF without known CAD [4]. We aimed to determine the frequency of CAD in HFrEF patients of unknown etiology and without known CAD, and to identify variables associated with the presence and severity of CAD.